Effectiveness of furosemide in attenuating exercise‐induced pulmonary haemorrhage in horses when administered at 4‐ and 24‐h prior to high‐speed training. (3rd November 2017) - Knych, H. K.; Wilson, W. D.; Vale, A.; Kass, P. H.; Arthur, R. M.; Jones, J. H.
Summary: Background: Due to the high prevalence of EIPH in racehorses and its potential impact on the horse's health, furosemide administration is permitted up to 4‐h prior to post time in most North American racing jurisdictions. Anecdotal reports suggest that administration of furosemide 24‐h prior to strenuous exercise may be equally effective in decreasing the severity of EIPH. Objectives: To 1) compare the efficacy of furosemide in reducing the presence and severity of EIPH when administered 4‐ or 24‐h prior to strenuous exercise 2) characterise electrolyte and blood parameters following administration of furosemide at 4‐ and 24‐h prior to exercise. Study design: 3‐way crossover. Methods: Fifteen Thoroughbred racehorses received 5 mL of 0.9% NaCl or 250 mg of furosemide either 4‐ or 24‐h prior to a 5‐furlong simulated race. Blood samples were collected prior to and post‐run for determination of furosemide, lactate, haemoglobin and electrolyte concentrations. One‐hour post‐race, an endoscopic exam and bronchoalveolar lavage (BAL) were performed. Horses were assigned an EIPH score based on predetermined criteria and the number of red blood cells in BAL fluid was determined. Results: Endoscopic EIPH scores were lower in the 4‐h vs. the 24‐h (P   =   0.03) furosemide groups. RBC counts in BAL fluid were lower in the 4‐h furosemide vs. saline treatment groups (P   =   0.01) but no difference was noted between the saline and 24‐h furosemide groups (P   =   0.3), nor between the 4‐ and 24‐h groups (P   =   0.5). Main limitations: Small sample size and large range of running times for the 5‐furlong work. Conclusions: While none of the treatments prevented EIPH, endoscopic scores and RBC counts in BAL fluid support the efficacy of furosemide in reducing the severity of EIPH. Endoscopic scores were lower in the 4‐h furosemide group compared with 24‐h administration. Red blood cell counts were lower in the 4‐h furosemide group compared with saline treatment.